Shopping Center/Shopping Mall: Architecture of the Spectacle, Abstract Machine and Urbanism in the 21st Century - Kaewlai, Peeradorn (Journal of Architectural/Planning Research and Studies (JARS), 2002)
Since the development of the “department store” and through Industrial Revolution, consumer culture has been changed to that of consumerism of the western society in the 19th Century. Mass production has tended to accommodate society at large, and the rise of middle-class people has also claimed for identity in social structure. At these crossing points, a new kind of “public space” has been formed and privately owned by private sector. The shopping center/shopping mall has transformed shopping activity into experience in any environmental setting. The new mechanism of the society could fuse trade with desire under the logic of consumerism. The formation of such places does not only appear in the building form, but also reconstitutes itself as a new kind of public space that fully integrates many services for urban activities. It becomes an architecture that determines behavior and shapes the attitude of the people towards consumerism. By using “image culture” which has been embedded in everyday urbanism and combining with the logic of post-modern architecture, shopping center/shopping mall becomes “signifier” of environment, which can attract every consumer. As a social mechanism, it has become an important urban instrument for every city in the 21st century.